Species composition and conservation values of mammal fauna in the Xuan Son national park, Phu Tho province - Dang, Nguyen Xuan (Academia Journal of Biology, 2006)
Based on results of mammal surveys conducted in 2000, 2003, 2004 and 2005 by the Department of vertebrate Zoology (Institute of Ecology and Biological resources) and reviews of previous mammal surveys of other authors, a list of 76 mammal species belonging to 24 families of 8 orders has been compiled for the Xuanson national park (NP), Phutho province. Among these species, 16 species are endemic of the indochinese sub-region, 20 species enlisted in the 2004 IUCN list, 25 species enlisted in the Red Data Book of Vietnam (2000) and 17 species enlisted in the Governmental Decree 48/2002/NDCP. The Xuan Son NP is especially important for the bat conservation due to the existence of a system of large caves covered by tall forests. The mammal fauna of the Xuan Son NP has been degraded in number and is threatened by illegal hunting, habitat disturbance and domestic cattle raising. Recommendations for the improvement of the mammal conservation in the Xuan Son NP are provided.